The Spanish rural school from the New Rural paradigm. Evolution and challenges for the future - Morales-Romo, Noelia (Revista Colombiana de Ciencias Sociales, 2017)
This paper focuses on the Spanish research exploring the role of schools in rural areas from the prospect of the New Rurality. It seeks to reflect on the context in which these schools are located and emphasise knowledge thereof. Method: Based on both, qualitative and quantitative methodology, 225 Spanish schools were interviewed and two surveys were applied (personal and online) to teachers, parents and head teachers. Results: The data reflect the reality of schools in rural environments in terms of educational policies, traditional aspects such as transport and resources, needs, advantages and disadvantages and their possible evolution in the future. Conclusions: This paper contributes to the presentation of a current overview of rural schools exempt from stereotypes and focused on educational policies, their schools’ needs and the demystification of false beliefs, while describing defining elements such as the more symbolic than real value, its excessive dependence on teachers working in them or their bureaucratic higher profile versus their urban counterparts. © Revista Colombiana de Ciencias Sociales.